Sheep grazing and soil bacterial diversity in shrublands of the Patagonian Monte, Argentina - Olivera, Nelda Lila (2016)
Our objective was to assess whether long-term continuous sheep grazing was associated with the bacterial community of the Patagonian Monte soils. We randomly extracted soil samples from 5 plant-covered patches (PCP) and the nearest inter-canopy areas (IC) at sites with low (L), moderate (M) and heavy (H) grazing intensity. Bacterial communities were evaluated by denaturing gradient gel electrophoresis (DGGE) and dominant bands were sequenced. Dendrograms showed a different association among grazing sites in PCP compared to IC areas. In PCP, M and H sites were clustered and DGGE revealed a high similarity in the bacterial community regardless of grazing intensity. In IC areas, analyses clustered L and M sites. Band sequencing revealed that members of these communities belonged to Sphingobacteria, Solibacteres, Gammaproteobacteria, Betaproteobacteria and Bacilli. Some of the band sequences related to Nitrosococcus oceani and Nitrosococcus watsonii which are restricted to marine environments and salt lakes. Microcoleus vaginatus and diatom chloroplast-related sequences were mainly detected in IC areas from L and M. Heavy grazing could alter autotrophic bacteria/diatom composition in IC areas possibly due to physical disturbance of biological crusts by trampling, threatening the potential of crust re-formation. Grazing intensity affected soil bacterial communities differently in PCP and IC areas with soil crust, highlighting the importance of improving our understanding of microbial diversity responses to land use.